THE INFLUENCE OF TEACHER’S PERSONALITY TOWARD STUDENTS’ MOTIVATION IN LEARNING ENGLISH SCIENCE CLASS OF SMAN 1 PADEMAWU - Kurratul Aini; Kuntum Khoiroh Ummah (Dewan Pendidikan Pamekasan, 2022)
Teacher is very important aspect in the teaching learning process. The success of students in obtaining knowledge when studying at class is strongly influenced by their teacher as a facilitator of learning and a person who transfer his knowledge. Teacher personality is one of the aspects that will get students’ perception and impression. By having a good personality, the students will have good opinion and good thinking about their theacher that will support them to increase their motivation in mastering subjects. However, when the students get negative impression about their teacher, it of course will decrease their motivation in learning English. In short, a good teacher must have positive attitude, can be a good example for his students, and be professional in his job. Concerning with those fact above, this research focuses on analyzing whether teacher’s personality can influence the students’ motivation in learning English at the eleventh science class of SMAN I Pademawu This research was designed by using descriptive quantitative research. The researcher took all of the eleventh science class of SMAN 1 Pademawu as the population. It consists of two classes, those are XI-A1 and XI-A2 class. There are 39 students in XI-A1 class and 38 students in XI-A2 class. But for this research, the researcher just took XI-A2 class as the example because this class is the excellent science class. To collect the data, the writer used observation, interview, questionnaire and documentation. To analyze the data result of questionnaire, the researcher used the formula of product moment, and using words to deskribe the result of interview. The calculation of r-xy score is 0,557, while the r-table at the degree of significance 5% is 0,325. From the result of this calculation, the researcher concluded that the r-score is higher than r-table. It means that there is significant influence of teacher’s personality toward students’ motivation in learning English at the eleventh science class of SMAN 1 Pademawu. Beside that, the result of interview to both students and the teacher also supported the researher’s conclusion. It could be concluded that teacher’s pesonality can influence the students’ motivation in learning English. In other words, the alternative hyphotesis of this research is accepted. It is hopefully that this research will give an inspiration for all of the teachers to concern more about their personality in supporting the students’ motivation. Moreover, the findings will become a base for further researcher to conduct a more comprehensive research related to this study.